Bisphenol S Induces Lipid Metabolism Disorders in HepG2 and SK-Hep-1 Cells via Oxidative Stress - Kai-Xing Lin; Zi-Yao Wu; Mei-Lin Qin; Huai-Cai Zeng (Toxics)
Bisphenol S (BPS) is a typical endocrine disruptor associated with obesity. To observe BPS effects on lipid metabolism in HepG2 and SK-Hep-1 human HCC cells, a CCK-8 assay was used to assess cell proliferation in response to BPS, and the optimal concentration of BPS was selected. Biochemical indices such as triglyceride (TG) and total cholesterol (T-CHO), and oxidative stress indices such as malondialdehyde (MDA) and catalase (CAT) were measured. ROS and MDA levels were significantly increased after BPS treatment for 24 h and 48 h (p < 0.05), indicating an oxidative stress response. Alanine aminotransferase (ALT), T-CHO, and low-density lipoprotein cholesterol (LDL-C) levels also increased significantly after 24 or 48 h BPS treatments (p < 0.05). RT-PCR and Western blot analyses detected mRNA or protein expression levels of peroxisome proliferator-activated receptor α (PPARα) and sterol regulatory element-binding protein 1c (SREBP1C). The results indicated that BPS could inhibit the mRNA expression of PPARα and carnitine palmitoyl transferase 1B (CPT1B), reduce lipid metabolism, promote mRNA or protein expression of SREBP1C and fatty acid synthase (FASN), and increase lipid synthesis. Increased lipid droplets were observed using morphological Oil Red O staining. Our study demonstrates that BPS may cause lipid accumulation by increasing oxidative stress and perturbing cellular lipid metabolism.